2012
DOI: 10.1016/j.rmed.2011.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Sleep desaturation and its relationship to lung function, exercise and quality of life in LAM

Abstract: Significant hypoxaemia during sleep is common in LAM patients with normal SpO(2) while awake, especially among those with some degree of hyperinflation in lung function tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 36 publications
(18 reference statements)
0
3
0
1
Order By: Relevance
“…12 Desaturation during sleep has been well studied in chronic respiratory diseases such as COPD and lymphangioleiomyomatosis (LAM), but it has been poorly studied in IPF. 40,41 It was shown that patients with mild daytime hypoxemia may be particularly vulnerable to desaturation during sleep because they often reside on the steep portion of the oxyhemoglobin dissociation curve. COPD-OSA overlap syndrome patients have more pronounced nocturnal hypoxemia and are at increased risk of death.…”
Section: Discussionmentioning
confidence: 99%
“…12 Desaturation during sleep has been well studied in chronic respiratory diseases such as COPD and lymphangioleiomyomatosis (LAM), but it has been poorly studied in IPF. 40,41 It was shown that patients with mild daytime hypoxemia may be particularly vulnerable to desaturation during sleep because they often reside on the steep portion of the oxyhemoglobin dissociation curve. COPD-OSA overlap syndrome patients have more pronounced nocturnal hypoxemia and are at increased risk of death.…”
Section: Discussionmentioning
confidence: 99%
“…Dyspnea and lower exercise capacity may be associated with several factors, such as dynamic hyperinflation, worsening gas exchange and, potentially, pulmonary hypertension (PH). Hypoxemia may occur at rest, during exercise or even during sleep, mainly in those patients with a higher degree of impairment in pulmonary function tests (PFTs) [5, 7, 8]. …”
Section: Introductionmentioning
confidence: 99%
“…Pulmonary function tests (PFTs) show an obstructive pattern and reduced diffusion capacity [ 12 ]. Hypoxemia during sleep is a common finding [ 13 ]. Chest X-Ray is normal in most patients with LAM unless there is a complication due to pleural effusions or pneumothorax.…”
Section: Discussionmentioning
confidence: 99%